Tetris (2020)
Tetris is a project located in Bogotá between the neighborhoods Los Andes and Rio Negro. It is a building that combines a marketplace, a child development center, retail stores, commerce, and housing. It is a hybrid architecture proposal that aims to be the articulator of two neighborhoods that are not connected in any way despite being next to each other. The objective of the project is to improve connectivity in the sector and generate greater interaction and activity between the two sectors by intensifying their activity and urban relationship.